Indirect Spectrophotometric Determination of Tolnaftate in Pharmaceutical Preparations - Thair Tahssen; Nief Rahman Ahmed (مجلة التربية والعلم, 2009)
Abstract A highly, sensitive, indirect spectrophotometric method has been develop for the determination of tolnaftate in pharmaceutical preparations. The method is based on the oxidation of tolnaftate with Fe(III) in acidic medium. Fe (III) subsequently reduces to Fe(II),which is coupled with potassium ferricyanide after heating for 10 minutes at 70 0C to form prussian blue and the absorbance of the product was measured at 785 nm against a reagent blank. Beer's law was obeyed in the range of 0.02-0.16 ppm with molar absorptivity of 1.7 x106 L.mol-1.cm-1, relative standard deviation of the method was less than 2.5% and accuracy (average recovery %) was 100.3%. The effect of various factors such as temperature, heating time,concentration of reagents, and interferences were investigated to optimize the procedure. The proposed method has been applied for the determination of tolnaftate in pharmaceutical preparations (quadrim cream and topical solution). A statistical compartsion of these results with those of official method shows good agreement using "t" and "F" test at 95% confidence level. the results indicated that there is no systematic error and the present method has good validity.